Role of Third Party Interference in Marital Stability among Married adults in Nigeria - Adebayo, David Obafemi; Blessing, Ifeoluwa; Faysol, Faysol (Buletin Konseling Inovatif, 2025)
This study explored the role of third-party interference in achieving marital stability among married adults, examining both its positive and negative impacts. The study identified key sources of third-party involvement, including family members, friends, and professional counsellors, and evaluated how these parties influence marital relationships resulting to stability in marriages. The findings suggested that while third-party interference may provide essential support during crises periods, such as financial difficulties or health challenges, it could also create significant challenges. These include the erosion of the couple's autonomy, increased conflict, and dependence on external sources for advice. Moreover, biased interference from family members or friends could lead to division within the marriage, causing either or both partners to feel unsupported. The research further explored the strategies for managing third-party interference, highlighting the importance of open communication between spouses, setting boundaries, and seeking professional counselling when necessary. A united front and a clear understanding of the couple’s priorities are also crucial in preventing external involvement from destabilizing the marital relationship. The study concluded that while third-party interference is often inevitable especially in a marital bliss, the way and manner in which it is managed greatly determines its impact on the stability of such homes. By employing effective strategies, couples could navigate external pressures and maintain a strong, stable relationship. The implication of this study is that it would most likely provide valuable insights for married adults, relationship/marriage counsellors, and family therapists who work to promote marital stability in the face of external interferences or aggression.